Análise de eficiência energética em rolamentos radiais de esferas - Rocha, Iuri de Souza (2019)
There are more than 20 billion lubricated bearings in the world. It is estimated that 80% of the premature failure of these bearings is due to lubrication problems, in particular, the inadequate choice of a lubricant. Such choice can also lead to higher energy consumption. Considering the world scenario of search for energy saving, the understanding of energy dissipation of bearings becomes a relevant topic of study. In this context, a didactic tool was developed to evaluate the efficiency of bearings in Matlab. Such a tool can be run on computers without software installation and allows analyzing the effects of lubricant selection as well as operating conditions on the formation of lubricating film and friction losses. All entries and results are explained in detail in the tool.